Sixty Alleles of the ALS7 Open Reading Frame in Candida albicans: ALS7 Is a Hypermutable Contingency Locus - Zhang, Ningxin (Cold Spring Harbor Laboratory Press, 2003)
The ALS (agglutinin-like sequence) gene family encodes proteins that play a role in adherence of the yeast Candida albicans to endothelial and epithelial cells. The proteins are proposed as virulence factors for this important fungal pathogen of humans. We analyzed 66 C. albicans strains, representing a worldwide collection of 266 infection-causing isolates, and discovered 60 alleles of the ALS7 open reading frame (ORF). Differences between alleles were largely caused by rearrangements of repeat elements in the so-called tandem repeat domain (21 different types occurred) and the VASES region (19 different types). C. albicans is diploid, and combinations of ALS7 alleles generated 49 different genotypes. ALS7 expression was detected in samples isolated directly from five oral candidosis patients. ORFs in the opposite direction contained within the ALS7 ORF were also transcribed in all strains tested. Isolates representing a more pathogenic general-purpose genotype (GPG) cluster of strains tended to have more tandem repeats than other strains. Two types of VASES regions were largely exclusive to GPG strains; the remaining types were largely exclusive to noncluster strains. Our results provide evidence that ALS7 is a hypermutable contingency locus and important for the success of C. albicans as an opportunistic pathogen of humans.